Corticosteroid infiltration in partial distal biceps ruptures - Elisabeth A. Wörner; Elisa L. Zwerus; Ante Prkic; Femke M.A.P. Claessen; Bertram The; Denise Eygendaal (Clinics in shoulder and elbow, 2025)
Background: Little is known about the potential negative or positive effects of peritendinous infiltration with corticosteroids in the non-surgical treatment of partial distal biceps tendon tears. Peritendinous fluid, synovitis, and bursitis often accompany partial tears and can be a source of persistent pain. We hypothesize that peritendinous corticosteroid infiltration is a safe non-surgical treatment option for complaints related to a partial distal biceps tendon rupture.Methods: A single-center retrospective analysis was performed on a cohort of 52 patients with partial distal biceps tears (<50% of the footprint involved), as confirmed by magnetic resonance imaging. All patients received an ultrasound-guided intrabursal peritendinous infiltration with 1 mL of triamcinolone acetonide (10 mg/mL) and 4 mL of lidocaine (HCl 2%). Patient files were reviewed for demographic information, date of injury, injury mechanism, treatment modality (operative or nonoperative), clinical follow-up (2011–2021), and complications, including progression to a complete rupture. Results: The median duration of follow-up after infiltration was 15 months (1.2–45 months). No infiltration-related complications were observed following infiltration therapy. Surgical reconstruction was ultimately performed in 65% of the patients with a partial tear. One patient sustained a trauma to the elbow in the weeks following infiltration, resulting in a complete tear. Conclusions: Infiltration with corticosteroids is a safe treatment option for patients with a partial tear of the distal biceps who failed progressive exercise therapy. Surgical reconstruction was avoided in 35% of patients following infiltration treatment.Level of evidence: IV. KCI Citation Count: 0